Personality traits have an effect on pain-related psychological variables in patients with chronic low back pain - Kazuhiro Hayashi; Kenji Miki; Yui Fukushima; Mayuu Iwai; Yukiko Shiro; Tomoko Tetsunaga; Toshifumi Takasusuki; Masako Hosoi; Masao Yukioka; Seiji Okada (PLoS ONE, 2026)
Introduction An association between personality factors and pain experience has been investigated. However, the direct contributions of personality traits by the Maudsley Personality Inventory to clinical pain outcomes in patients with chronic pain remain unclear. The Maudsley Personality Inventory is a self-report questionnaire used to assess extroversion, neurotic tendencies, and lying or exhibitionistic tendencies. The present study aimed to investigate whether personality traits influenced with the pain-related psychological variables in patients with chronic secondary low back pain (CLBP). Methods One hundred fifteen consecutive outpatients with CLBP were included. Personality traits were measured by using the Maudsley Personality Inventory to assess extroversion, neurotic tendencies, and lying or exhibitionistic tendencies. The association of Maudsley neurotic tendency score and pain-related variables was analyzed and then performed a path analysis. Eleven patients (9%) were the biased persons with frequent lying. Results The pain-related variables showed no significant differences between the persons with frequent lying and those with normal. The Maudsley neurotic tendency score was significantly associated with Pain Catastrophizing Scale, Hospital Anxiety and Depression Scale, Pain Self-Efficacy Questionnaire, Athens Insomnia Scale, and EuroQol-5 Dimensions-3 level. The unstandardized coefficients for Maudsley neurotic tendency score were small, compared to pain-Numerical Rating Scale in each outcome. Conclusions These results suggest the presence of neurotic tendency could have an impact on the health outcomes in patients with CLBP, but the impact was small.